2015
DOI: 10.1242/dmm.019042
|View full text |Cite
|
Sign up to set email alerts
|

Iron is a specific cofactor for distinct oxidation- and aggregation-dependent Aβ toxicity mechanisms

Abstract: Metals, including iron, are present at high concentrations in amyloid plaques in individuals with Alzheimer's disease, where they are also thought to be cofactors in generating oxidative stress and modulating amyloid formation. In this study, we present data from several Drosophila models of neurodegenerative proteinopathies indicating that the interaction between iron and amyloid beta peptide (Aβ) is specific and is not seen for other aggregation-prone polypeptides. The interaction with iron is likely to be i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 106 publications
1
19
1
Order By: Relevance
“…This result finds support in the morphological analysis, where aggregates of Aβ1–42 in presence of Fe III ‐citrate are organized in tangles of short fibrils differently from the long and more structured fibers observed in iron absence. Differently from the conclusions of some works reported in literature, we find that Fe(III) accelerates the kinetics of aggregation as other authors reported . We speculate that the seeds of nucleation induced by Iron citrate are different from those formed in the absence of metal, so the pathway of aggregation does not bring to the formation of long fibrils, but only to short and segmented fibrils.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This result finds support in the morphological analysis, where aggregates of Aβ1–42 in presence of Fe III ‐citrate are organized in tangles of short fibrils differently from the long and more structured fibers observed in iron absence. Differently from the conclusions of some works reported in literature, we find that Fe(III) accelerates the kinetics of aggregation as other authors reported . We speculate that the seeds of nucleation induced by Iron citrate are different from those formed in the absence of metal, so the pathway of aggregation does not bring to the formation of long fibrils, but only to short and segmented fibrils.…”
Section: Discussioncontrasting
confidence: 99%
“…[22,31] To unravel the molecular mechanism of the interaction between Fe(III) and Ab, we examined how three Ab peptides (Ab1- for AbpE3-42, where there is a big amount of not ordered structure and the b-sheets are exclusively antiparallel, characteristic of toxic aggregates, [20] , [57] the decrease of b-pleated sheet and consequently of ThT fluorescence is minimal. It has been reported that Fe(III) impedes structural progression such that the Ab1-42 remains in intermediate conformations for longer, generating amorphous aggregates, [58] and delaying the formation of mature amyloid structures [59] as shown for Cu(II). [60] This conformational change is associated with decreased exposure of hydrophobic clusters.…”
Section: Discussionmentioning
confidence: 95%
“…As previously described, iron deposition within plaques hints at a role of iron in plaque genesis and/or propagation. These ex vivo data are supported by in vitro findings demonstrating that iron can accelerate the aggregation of the Aβ peptide (Huang et al, 1999;Liu et al, 2011;Mantyh et al, 1993;Ott, Dziadulewicz, & Crowther, 2015), which is prevented by iron chelation (Huang et al, 2004). Iron therefore has the ability to cause Aβ aggregation, and the fact that iron is enriched in plaques provides the "smoking gun" evidence that iron is involved in plaque genesis.…”
Section: Mechanisms Of Iron In the Pathogenesis Of Admentioning
confidence: 71%
“…In the other models, human AβPP is co‐expressed with human BACE1 allowing the production of C99 and different isoforms of the Aβ peptide (including post‐translationally modified Aβ variants) through the processing of human AβPP by human BACE1 and by endogenous fly γ‐secretase (the AβPP‐BACE1 fly model) . AD fly models have been frequently used during the last two decades to investigate Aβ toxicity, cell‐specific vulnerability and aggregation . However, potential differences in the toxic mechanisms between the two different AD fly models have not been thoroughly investigated.…”
mentioning
confidence: 99%